Ketchup clouds : a novel - Pitcher, Annabel (New York, N.Y. : Little, Brown and Company, 2013)
Zoe, a teenager in Bath, England, writes letters to a death-row inmate in Texas, hoping to find comfort in sharing her guilty secret over the death of a friend with someone who can never tell her family.
Originally published: London : Indigo, 2012.
Keywords: Guilt -- Juvenile fiction; Grief -- Juvenile fiction; Families -- England -- Juvenile fiction; Children's secrets -- Juvenile fiction; Epistolary fiction; Guilt -- Fiction; Grief -- Fiction; Family life -- England -- Fiction; Secrets -- Fiction; Letters -- Fiction; Bath (England) -- Juvenile fiction; Bath (England) -- Fiction; England -- Fiction; Epistolary fiction